Dealing with the Balanced Academic Curriculum Problem Considering the Chilean Academic Credit Transfer System - Inostroza-Ponta, M; Vasquez-Perez, O; Villalobos-Cid, M (IEEE Computer Society, 2019)
The curricular design of the academic programs and the distribution of the academic load has become a controversial topic since it is related to the health and performance of the students. In Chile, the load of the academic programs has to be distributed and balanced according to the Chilean Academic Credit Transfer System recommendations. The Balanced academic curriculum problem has been studied in computer science, being defined as the assignation of courses to academic periods satisfying all the prerequisite constraints. In this work, we implement two strategies to deal with this problem, a quadratic integer programming model and a genetic algorithm approach, and evaluate them using well-know data sets from the literature. Next, these strategies are adapted to study the balance of the load of six real engineering academic programs according to the Chilean credit references. The results show that both approaches obtained the optimal solutions for the literature data sets, and were able to find solutions which improve the balance of the real academic programs, distributing uniformly the load between periods. © 2019 IEEE.